UPAYA PERLUASAN PANGSA PASAR PRODUK UMKM KELOMPOK TENUN GUMESA DI DESA GIRI TEMBESI MELALUI DIGITAL MARKETING DAN INOVASI KEMASAN - Yomi, Arda; Dwianto, Yogik; Lestari, Zausan Maulia; Maulana, M. Shagiar; Karunia, Insan Mulia; Fitrianingsih, Sri Ayu; Himi, Lestin Eliana; Subhiandari, Baiq Nada; Salwa, Ummi Raehanatul; Rejeki P., Mayada Dwi (Jurnal Wicara Desa, 2023)
Real Work Lecture or KKN is an implementation and concretization of community service which is one of the three pillars of high education. Through the village community service activities in Giri Tembesi Village, it is hoped that there will be a transfer of knowledge related to digital marketing and packaging innovation. The purpose of this activity is to provide understanding to the village community about the importance of digital marketing and packaging innovation to expand the potential market for small and micro bussines products in the village. To raise this awareness, structured efforts were made in the form of counseling or outreach, to direct assistance to one of the small business, namely the Dharma Yasa Group. The results of these activities indicate an increase in the understanding of small business actors on the importance of digital marketing and packaging innovation.